PENGARUH MEDIA EDUKASI VIDEO TERHADAP KETERAMPILAN KADER POSYANDU DALAM PENGGUNAAN APLIKASI E-PPGBM (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: The importance of providing information about individual nutritional status can be fulfilled by using the online application system for recording and reporting on community-based nutrition (E-PPGBM). Posyandu cadres in the working area of ​​the Katapang Health Center still have problems using the E-PPGBM application due to the lack of socialization about the application and the lack of skills of posyandu cadres. Therefore, it is necessary to increase the skills of posyandu cadres in the use of the E-PPGBM application through video education media. Purpose: Knowing the impact of video education media on the skills of posyandu cadres in the use of the E-PPGBM application in the working area of ​​the Katapang Health Center. Methods: The research used a quasi-experimental design with one group pretest – posttest without control design. The population in this research were 51 posyandu cadres in the working area of ​​the Katapang Health Center, and the research sample was 34 posyandu cadres. The sample selection in this research was using a simple random sampling technique by drawing lots. Data analysis used the Wilxocon test to prove the research hypothesis. Results: The average skill score of the respondents before being given video education media was 70.0. The average score of respondents' skills after being given video education media was 93.5. The percentage increase in skills is 33.5%. The p value of the respondents' skills before and after being given video education media was (p = 0.000). Conclusion: There was a significant increase in skills after being given video education media to posyandu cadres in the working area of ​​the Katapang Health Center. Keywords: Nutritional Status; Skill; Community Health Services.